Primary writing tremor. - Bain PG; Findley LJ; Britton TC; Rothwell JC; Gresty MA; Thompson PD; Marsden CD; Bain, P G; Findley, L J; Britton, T C; Rothwell, J C; Gresty, M A; et al. (Brain: A Journal of Neurology, 1995)
Primary writing tremor (PWT) is considered to be a type of task-specific tremor in which tremor predominantly occurs and interferes with handwriting. We describe the clinical and neurophysiological features of 21 patients (20 male and one female) with PWT. Mean age at tremor onset was 50.1 years. A family history of PWT was obtained from seven patients. Ten patients obtained benefit from drug treatment (mainly propranalol or primidone) and seven responded to alcohol. The writing speeds of the patients (mean +/- SEM: 73.1 +/- 6.6 letters per minute) when using their preferred hand were significantly reduced (Student's t test: P < 0.001) compared with those of healthy control subjects (mean +/- SEM: 127.7 +/- 6.4). Surface polymyography performed during writing showed 4.1-7.3 Hz rhythmic activity predominantly in the intrinsic hand and forearm muscles. Alternating, extensor activation alone, skipping from alternating to extensor activation, and co-contracting EMG patterns were recorded from the flexor and extensor muscles of the forearm. There was no evidence for excessive 'overflow' of this rhythmic EMG activity, as similar activity was detected in comparable muscle groups of healthy control subjects. Accelerometry confirmed that the frequency of PWT ranged from 4.1-7.3 Hz (median 5.5 Hz) and that normal subjects wrote with a 4.0-7.7 Hz oscillation (median 4.6 Hz). Forearm reciprocal inhibition was normal in PWT (n = 13), and thus patients with PWT can be distinguished from those with writer's cramp in whom decreased presynaptic inhibition has been found. Patients were sub-classified as having either type A (n = 11) or B (n = 10) PWT depending on whether tremor appeared during writing (type A: task induced tremor) or whilst writing and adopting the hand position used in writing (type B: positionally sensitive tremor). However, the only differences between these two groups were that a co-contracting EMG pattern and tremor induced by tendon taps to the volar aspect of the wrist were present in type B but not type A cases.